Pharmacodynamics of 2 dosages of orally administered esomeprazole in client‐owned, healthy dogs: A prospective, crossover study - Abby Ostronic; Christine Gremillion; Song Zhang; Joerg M. Steiner; M. Katherine Tolbert; Emily N. Gould (Journal of Veterinary Internal Medicine)
Abstract Background Esomeprazole use is increasing in dogs, but the gastrointestinal adverse events associated with q12h dosing necessitate pharmacodynamic evaluation of a reduced dose and frequency of administration. Objectives To compare the efficacy of 2 doses of (q24h) esomeprazole in raising intragastric pH in dogs. Animals Nine healthy, client‐owned dogs, >20 kg. Methods Prospective, randomized, double blinded, crossover study. Esomeprazole (0.5 or 1 mg/kg q24h) was orally administered for up to 5 days per treatment arm, and the mean percentage time intragastric pH was ≥3 (MPT3) and ≥4 (MPT4) for 24 hours periods were compared to pretreatment pH using a continuous pH monitoring system. Dogs failing to reach pH goals (MPT3 ≥75%, MPT4 ≥66%) with once daily dosing received esomeprazole 1 mg/kg PO q12h to determine if a higher dose would improve acid suppression. Results No significant difference in the MPT3 or MPT4 was identified between treatments for any time point (P > .05). Both doses increased the MPT pH ≥3 and 4 median [range] (0.5 mg/kg, 1 mg/kg) on days 1 (MPT3: 76.8% [44‐100], 69.2% [28.2‐100]; MPT4: 65.6% [16.7‐99.3], 54.9% [14.9‐93.3]; P = .0009) and 2 (MPT3:77.2% [27.4‐100], 75.4% [49.4‐89.5]; MPT4: 66.3% [15.5‐100], 59.7% [33.8‐81.2]; P = .0005) of PPI treatment compared to pretreatment (MPT3: 58.3% [0.02‐93.9], 52.6% [6.1‐94.7]; MPT4: 25.2% [0‐86.8], 32.4% [1.8‐89.3]). Six dogs (66%, [0.36, 0.97]) reached pH goals established in humans with q24h dosing. Conclusions and Clinical Importance Both q24h PO esomeprazole doses were effective in raising intragastric pH, despite high intersubject variability, but 33% of dogs required q12h dosing to reach pH goals.